The OEIS is supported by the many generous donors to the OEIS Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A176606 Sequence defined by the recurrence formula a(n+1)=sum(a(p)*a(n-p)+k,p=0..n)+l for n>=1, with here a(0)=1, a(1)=3, k=0 and l=1. 2
 1, 3, 7, 24, 91, 376, 1635, 7377, 34197, 161876, 779125, 3801307, 18757219, 93444662, 469349303, 2374206202, 12084696935, 61848753886, 318082531211, 1643009103729, 8520055528453, 44338931718570, 231488012768833 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,2 LINKS FORMULA G.f f: f(z)=(1-sqrt(1-4*z*(a(0)-z*a(0)^2+z*a(1)+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z) (k=0, l=1). Conjecture: (n+1)*a(n) +2*(-3*n+1)*a(n-1) +(n+3)*a(n-2) +8*(n-3)*a(n-3) +4*(-n+4)*a(n-4)=0. - R. J. Mathar, Feb 29 2016 a(n) = Sum_{k=0..n} (C(k)*Sum_{j=0..n-k} (binomial(k+1,n-k-j)*binomial(-n+ 2*k+2*j,j))). - Vladimir Kruchinin, Apr 15 2016 EXAMPLE a(2)=2*3+1=7. a(3)=2*1*7+9+1=24. a(4)=2*1*24+2*3*7+1=91. MAPLE l:=1: : k := 0 : m:=3:d(0):=1:d(1):=m: for n from 1 to 28 do d(n+1):=sum(d(p)*d(n-p)+k, p=0..n)+l:od : taylor((1-sqrt(1-4*z*(d(0)-z*d(0)^2+z*m+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z), z=0, 31); seq(d(n), n=0..29): od; PROG (Maxima) a(n):=sum((binomial(2*k, k)*sum(binomial(k+1, n-k-j)*binomial(-n+2*k+2*j, j), j, 0, n-k))/(k+1), k, 0, n); /* Vladimir Kruchinin, Apr 15 2016 */ CROSSREFS Cf. A176604, A176605. Sequence in context: A228992 A246657 A038169 * A007172 A027610 A135688 Adjacent sequences:  A176603 A176604 A176605 * A176607 A176608 A176609 KEYWORD easy,nonn AUTHOR Richard Choulet, Apr 21 2010 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified May 27 16:48 EDT 2022. Contains 354110 sequences. (Running on oeis4.)